2023
DOI: 10.1021/acs.energyfuels.2c04221
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrodeoxygenation of Lignin-Derived Phenols to C6+ Cycloalkanols/Cycloalkanes over Magnetic Carbon-Encapsulated Nickel Nanospheres

Abstract: To obtain value-added fuels and chemicals from lignin, it is necessary to explore an efficient catalytic system for hydrodeoxygenation (HDO). In this study, a highly efficient and magnetically separable Ni@C catalyst was synthesized for conversion of lignin-derived phenols. Detailed results showed that the pyrolysis temperature played a crucial role in the difference of the carbon-defect degree, which increased the metal dispersion and the strong electronic metal−support interactions. Meanwhile, we revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that acidic sites play important roles in C-O bond dissociation by synergistically cooperating with redox-active metal sites, derived from their affinity to oxygencontaining groups in phenols. [18][19][20][21][22][23][24][25] However, the addition of liquid acids in catalytic systems is corrosive to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that acidic sites play important roles in C-O bond dissociation by synergistically cooperating with redox-active metal sites, derived from their affinity to oxygencontaining groups in phenols. [18][19][20][21][22][23][24][25] However, the addition of liquid acids in catalytic systems is corrosive to the environment.…”
Section: Introductionmentioning
confidence: 99%